A composite polymer film for current collector and its preparation method and application

By introducing polyolefin materials into the first and third layers of the polymer film, the high-temperature cycling performance problem of the battery caused by the dissolution of silica in the polymer film is solved, and better mechanical properties and high-temperature cycling performance are achieved.

CN118867264BActive Publication Date: 2025-04-25JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410898420.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-04-25
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The dissolution of silica in the polymer film causes poor battery charge and discharge cycling performance.

Method used

The polyolefin material is introduced into the first polymer layer and the third polymer layer without adding anti-adhesive silica, which reduces the polarity of the film and improves the surface roughness, and solves the problems of low adhesion and adhesion.

Benefits of technology

Improves the high-temperature cycling performance of current collectors during battery-end application and improves the mechanical properties of composite polymer films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004930211640000201
    Figure BDA0004930211640000201
  • Figure BDA0004930211640000211
    Figure BDA0004930211640000211
Patent Text Reader

Abstract

The present invention provides a composite polymer film for a current collector and a preparation method and application thereof, wherein the composite polymer film comprises a first polymer layer, a second polymer layer and a third polymer layer stacked in sequence; wherein the materials of the first polymer layer and the third polymer layer are both a combination of a first polyester material and a polyolefin material, and the material of the second polymer layer is a second polyester material; in the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80); in the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80); in the second polymer layer, the content of the second polyester material is 100wt%. The present invention can reduce the polarity of the composite polymer film, solve the problem of film surface adhesion, solve the problem of low bonding between the metal layer and the composite polymer film, and improve the high temperature cycle performance of the current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and specifically relates to a composite polymer film for current collector and a preparation method and application thereof Background Art

[0002] At present, composite current collectors based on polymer films have received widespread attention and application in the new energy industry. The preparation process of the composite current collector is usually: a layer of metal (aluminum, copper, etc.) material is deposited on a polymer film (such as polypropylene, polyethylene, polyester, etc.) by physical vapor deposition (PVD). The prepared surface metallized film with a certain conductivity is the composite current collector. Compared with traditional current collectors, composite current collectors based on polymer films have the characteristics of low cost, light weight, and good internal insulation. These characteristics enable the composite current collector to reduce the cost of the battery and improve the energy density and safety of the battery when used in the battery.

[0003] Among the many composite current collectors based on polymer films, composite current collectors based on polyester films are the most common. In the process of preparing polyester films, in order to prevent the film surfaces from sticking to each other during the winding process, an anti-adhesion agent, silica, is usually added. However, the silica introduced into the polyester film will be corroded by the electrolyte and its electrochemical reaction products during the high-temperature charge and discharge cycle of the battery, resulting in dissolution. The dissolution of silica and the consumption of the electrolyte and its electrochemical reaction products will cause the high-temperature charge and discharge cycle performance of the battery to deteriorate.

[0004] Therefore, it is urgent to design a new polymer membrane to solve the problem of dissolution of silicon dioxide in the polymer membrane, as well as the problem that the dissolution consumes the electrolyte and its electrochemical reaction products cause the high-temperature cycle performance of the battery to deteriorate. Summary of the invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a composite polymer film for current collectors, and a preparation method and application thereof. The present invention introduces polyolefin materials into the first polymer layer and the third polymer layer without adding anti-adhesive silica. On the one hand, it can reduce the polarity of the composite polymer film and improve the surface roughness of the composite polymer film, thereby solving the problem of film surface adhesion during the winding process caused by the lack of anti-adhesives; on the other hand, it solves the problem of low adhesion between the metal layer and the composite polymer film in the prepared current collector, and effectively improves the high-temperature cycle performance of the current collector during battery terminal application. In addition, the three-layer composite polymer film constructed by the present invention has good mechanical properties.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a composite polymer film for a current collector, the composite polymer film comprising a first polymer layer, a second polymer layer and a third polymer layer stacked in sequence;

[0008] Wherein, the materials of the first polymer layer and the third polymer layer are a combination of a first polyester material and a polyolefin material, and the material of the second polymer layer is a second polyester material;

[0009] In the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80);

[0010] In the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80);

[0011] In the second polymer layer, the content of the second polyester material is 100 wt %.

[0012] The present invention introduces polyolefin materials into the first polymer layer and the third polymer layer without adding anti-adhesive silica, which can reduce the polarity of the film on the one hand, and on the other hand, due to the introduction of polyolefin, the regular arrangement of polyester polymers is destroyed, thereby forming a higher roughness on the film surface, reducing the crystallinity of the film, and increasing the free volume of the film. Therefore, the introduction of polyolefin materials can not only solve the problem of film surface adhesion during the winding process caused by the lack of anti-adhesives, but also solve the problem of low adhesion between the metal layer and the composite polymer film in the current collector caused by the reduction of film polarity, thereby improving the high-temperature cycle performance of the current collector during the battery terminal application process. In addition, the three-layer composite polymer film constructed by the present invention has good mechanical properties.

[0013] In the first polymer layer of the present invention, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80), wherein the selection range of the first polyester material "20-60" can be, for example, 20, 25, 30, 35, 40, 45, 50, 55, 58 or 60, and the selection range of the polyolefin material "40-80" can be, for example, 40, 45, 50, 55, 60, 65, 70, 75 or 80, etc.

[0014] In the present invention, if the mass ratio of the first polyester material to the polyolefin material is too large, that is, the content of the polyolefin material is too low, the prepared composite polymer film will have severe sticking during the winding process and will easily stick when unwinding for use; if the mass ratio of the first polyester material to the polyolefin material is too small, that is, the content of the polyolefin material is too high, the surface tension of the prepared composite polymer film will decrease too much, resulting in poor adhesion between the metal layer and the composite polymer film in the subsequently prepared current collector, thereby causing the battery's charge and discharge cycle performance to deteriorate.

[0015] In the third polymer layer of the present invention, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80), wherein the selection range of the first polyester material "20-60" can be, for example, 20, 25, 30, 35, 40, 45, 50, 55, 58 or 60, and the selection range of the polyolefin material "40-80" can be, for example, 40, 45, 50, 55, 60, 65, 70, 75 or 80, etc.

[0016] In the present invention, if the mass ratio of the first polyester material to the polyolefin material is too large, that is, the content of the polyolefin material is too low, the prepared composite polymer film will have severe sticking during the winding process and will easily stick when unwinding for use; if the mass ratio of the first polyester material to the polyolefin material is too small, that is, the content of the polyolefin material is too high, the surface tension of the prepared composite polymer film will decrease too much, resulting in poor adhesion between the metal layer and the composite polymer film in the subsequently prepared current collector, thereby causing the battery's charge and discharge cycle performance to deteriorate.

[0017] As a preferred technical solution of the present invention, the first polyester material and the second polyester material independently include any one of polyethylene terephthalate, polyethylene 2,6-naphthalate, polybutylene terephthalate, poly-1,4-cyclohexanedimethanol terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol terephthalate, poly-2,6-naphthalate, poly-trimethylene terephthalate, poly-2,6-naphthalate, poly-butylene 2,5-furandicarboxylate or poly-butylene adipate terephthalate, or a combination of at least two thereof.

[0018] Preferably, the viscosity average molecular weight of the first polyester material and the second polyester material is independently 15000-50000 Da, for example, 15000 Da, 20000 Da, 25000 Da, 30000 Da, 35000 Da, 40000 Da, 45000 Da or 50000 Da.

[0019] In the present invention, if the viscosity average molecular weight of the polyester material is too low or too high, the film-forming property will be poor.

[0020] Preferably, the polyolefin material comprises any one of polyethylene, polypropylene, polystyrene, ethylene-propylene copolymer, ethylene-propylene-butene copolymer, or cycloolefin copolymer, or a combination of at least two thereof, preferably any one of random polypropylene, ethylene-propylene copolymer, ethylene-propylene-butene copolymer, or a combination of at least two thereof.

[0021] Preferably, the number average molecular weight of the polyolefin material is 10000-100000 Da, for example, it may be 10000 Da, 20000 Da, 40000 Da, 60000 Da, 80000 Da or 100000 Da.

[0022] In the present invention, if the number average molecular weight of the polyolefin material is too low or too high, the film-forming property will be poor.

[0023] As a preferred technical solution of the present invention, the thicknesses of the first polymer layer, the second polymer layer and the third polymer layer are respectively denoted as h1, h2 and h3, h1=h3, h1:h2=(1-15):(70-98), wherein the selection range of h1 "1-15" can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, and the selection range of h2 "70-98" can be, for example, 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90, 92, 94, 96 or 98, etc.

[0024] It should be noted that the introduction of polyolefins in the preparation process of the polymer film will lead to a decrease in the orientation and crystallinity of the polyester polymer during the stretching process, thereby deteriorating the mechanical properties. In order to solve this problem, the present invention designs a three-layer composite polymer film, in which the thickness of the second polymer layer is dominant, and the second polymer layer only contains polyester materials, so that a higher orientation and crystallinity can be obtained during the stretching process, ensuring that the prepared composite polymer film has good mechanical properties. If the ratio of h1 to h2 is too small, that is, the thickness of the first polymer layer or the third polymer layer is too thin, the production is difficult, and it is difficult to control the uniformity of the thickness, the anti-adhesion property deteriorates, and it is easy to stick to the film and break the film; if the ratio of h1 to h2 is too large, that is, the thickness of the first polymer layer or the third polymer layer is too thick, the mechanical properties of the prepared composite polymer film deteriorate.

[0025] Preferably, the thickness of the composite polymer film is ≥1 μm, for example, it can be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., preferably 2-20 μm.

[0026] In the present invention, considering that the thinner the composite polymer film is, the more it can promote the improvement of the energy density of the composite current collector, while taking into account the difficulty of production (the thinner the film is, the greater the production difficulty and the lower the yield), the preferred thickness of the composite polymer film is 2-20 μm.

[0027] In a second aspect, the present invention provides a method for preparing the composite polymer film as described in the first aspect, the preparation method comprising the following steps:

[0028] The raw materials for preparing the first polymer layer, the second polymer layer and the third polymer layer are respectively added into corresponding extrusion equipment, and after melt co-extrusion, they are successively subjected to sheet casting, stretching treatment and heat treatment, and the composite polymer film is obtained after winding.

[0029] The preparation method provided by the present invention is simple and easy to implement, and can be easily scaled up, and can effectively promote the promotion of the current collector at the application end.

[0030] It should be noted that the raw materials for preparing the first polymer layer, the second polymer layer and the third polymer layer are melted separately and then co-extruded from one die.

[0031] As a preferred technical solution of the present invention, before the raw materials for preparing the first polymer layer are added to the corresponding extrusion equipment, the raw materials for preparing the first polymer layer are pretreated, and the specific steps include:

[0032] The first polyester material is crystallized and dried, the polyolefin material is crystallized and dried, and then the dried first polyester material and the polyolefin material are mixed.

[0033] Preferably, during the pretreatment of the first polymer layer, the temperature for crystallization of the first polyester material is 130-200°C, for example, 130°C, 150°C, 170°C or 190°C, and the crystallization time is 20-130min, for example, 20min, 40min, 60min, 80min, 100min or 120min, etc.

[0034] In the present invention, the first polyester material is crystallized at 130-200° C. for 20-130 min, which can improve the crystallinity of the polymer and prevent adhesion during drying.

[0035] Preferably, during the pretreatment of the first polymer layer, the first polyester material is dried at a temperature of 130-180°C, for example, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, and the drying time is 110-300min, for example, 110min, 150min, 200min, 250min or 300min, etc.

[0036] In the present invention, drying is performed at 130-180° C. for 110-130 min, which can effectively remove moisture from the first polyester material and prevent the polymer from being oxidized during melt extrusion.

[0037] Preferably, during the pretreatment of the first polymer layer, the polyolefin material is crystallized at 60-100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C, and the crystallization time is 20-120min, for example, 20min, 40min, 60min, 80min, 100min or 120min.

[0038] In the present invention, the first polyester material is crystallized at 60-100° C. for 20-120 min, which can improve the crystallinity of the polymer and prevent adhesion during drying.

[0039] Preferably, during the pretreatment of the first polymer layer, the polyolefin material is dried at a temperature of 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, and the drying time is 100-300min, for example, 100min, 150min, 200min, 250min or 300min.

[0040] In the present invention, drying is performed at 60-80° C. for 100-300 min, which can effectively remove moisture from the first polyester material and prevent the polymer from being oxidized during melt extrusion.

[0041] Preferably, before the raw materials for preparing the second polymer layer are added to the corresponding extrusion equipment, the raw materials for preparing the second polymer layer are pretreated, and the specific steps include:

[0042] The second polyester material is crystallized and dried.

[0043] Preferably, during the pretreatment of the second polymer layer, the temperature for crystallization of the second polyester material is 130-200°C, for example, 130°C, 150°C, 170°C or 190°C, and the crystallization time is 20-130min, for example, 20min, 40min, 60min, 80min, 100min or 120min, etc.

[0044] In the present invention, the second polyester material is crystallized at 130-200° C. for 20-130 min, which can improve the crystallinity of the polymer and prevent adhesion during drying.

[0045] Preferably, during the pretreatment of the second polymer layer, the second polyester material is dried at a temperature of 130-180°C, for example, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, and the drying time is 110-300min, for example, 110min, 150min, 200min, 250min or 300min, etc.

[0046] In the present invention, drying is performed at 130-180° C. for 110-130 min, which can effectively remove moisture from the second polyester material and prevent the polymer from being oxidized during melt extrusion.

[0047] Preferably, before the raw materials for preparing the third polymer layer are added to the corresponding extrusion equipment, the raw materials for preparing the third polymer layer are pretreated, and the specific steps include:

[0048] The first polyester material is crystallized and dried, the polyolefin material is crystallized and dried, and then the dried first polyester material and the polyolefin material are mixed.

[0049] Preferably, during the pretreatment of the first polymer layer, the polyolefin material is crystallized at 60-100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C, and the crystallization time is 20-120min, for example, 20min, 40min, 60min, 80min, 100min or 120min.

[0050] In the present invention, the first polyester material is crystallized at 60-100° C. for 20-120 min, which can improve the crystallinity of the polymer and prevent adhesion during drying.

[0051] Preferably, during the pretreatment of the first polymer layer, the polyolefin material is dried at a temperature of 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, and the drying time is 100-300min, for example, 100min, 150min, 200min, 250min or 300min.

[0052] In the present invention, drying is performed at 60-80° C. for 100-300 min, which can effectively remove moisture from the first polyester material and prevent the polymer from being oxidized during melt extrusion.

[0053] Preferably, during the melt co-extrusion process, the heating and melting temperature is 270-290°C, for example, 270°C, 280°C or 290°C.

[0054] Preferably, during the melt co-extrusion process, the volume ratio of the extrusion amounts of raw materials for preparing the first polymer layer, the second polymer layer and the third polymer layer is (1-15):(70-98):(1-15), wherein the selection range of the extrusion amount of the first polymer layer "1-15" can be, for example, 1, 3, 5, 7, 9, 11, 13 or 15, etc., the selection range of the extrusion amount of the first polymer layer "70-98" can be, for example, 70, 75, 80, 85, 90, 95 or 98, etc., and the selection range of the extrusion amount of the third polymer layer "1-15" can be, for example, 1, 3, 5, 7, 9, 11, 13 or 15, etc.

[0055] Preferably, the stretching treatment includes longitudinal stretching and transverse stretching.

[0056] Preferably, the step of longitudinally stretching comprises:

[0057] Preheating, then longitudinal stretching, and cooling after stretching.

[0058] Preferably, the preheating temperature is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C.

[0059] Preferably, the cooling temperature is 30-50°C, for example, 30°C, 40°C or 50°C.

[0060] Preferably, the stretching ratio of the longitudinal stretching is (3-6):1, for example, it can be 3:1, 4:1, 5:1 or 6:1, etc., the stretching temperature of the longitudinal stretching is 80-110°C, for example, it can be 80°C, 90°C, 100°C, or 110°C, etc., the stretching ratio of the transverse stretching is (2-4):1, for example, it can be 2:1, 3:1 or 4:1, etc., and the stretching temperature of the transverse stretching is 80-110°C, for example, it can be 80°C, 90°C, 100°C or 110°C, etc.

[0061] Preferably, during the transverse stretching process, the preheating temperature is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, and the cooling temperature is 40-70°C, for example, 40°C, 50°C, 60°C or 70°C.

[0062] Preferably, the heat treatment temperature is 70-100°C, for example, 70°C, 80°C, 90°C or 100°C.

[0063] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0064] (1) pretreating the raw materials for preparing the first polymer layer, specifically comprising: crystallizing the first polyester material at 130-200° C. for 20-130 min, then drying at 130-180° C. for 110-300 min, crystallizing the polyolefin material at 60-100° C. for 20-120 min, then drying at 60-80° C. for 100-300 min, and then mixing the dried first polyester material and the polyolefin material to obtain a first material;

[0065] The raw materials for preparing the second polymer layer are pretreated, and the specific steps include:

[0066] The second polyester material is crystallized at 130-200° C. for 20-130 min, and then dried at 130-180° C. for 110-300 min to obtain a second material;

[0067] The raw materials for preparing the third polymer layer are pretreated, and the specific steps include:

[0068] The first polyester material is crystallized at 130-200° C. for 20-130 min, and then dried at 130-180° C. for 110-300 min, the polyolefin material is crystallized at 60-100° C. for 20-120 min, and then dried at 60-80° C. for 100-300 min, and then the dried first polyester material and the polyolefin material are mixed to obtain a third material;

[0069] (2) conveying the first material, the second material and the third material to corresponding twin-screw extruders respectively, heating and melting at 270-290° C., filtering and co-extruding through a die to obtain molten materials;

[0070] Wherein, the volume ratio of the extrusion amount of the first material, the second material and the third material is (1-15):(70-98):(1-15);

[0071] (3) casting the molten material onto a casting roll, and cooling the molten material at 20-60° C. (e.g., 20° C., 30° C., 40° C., 50° C., or 60° C.) to obtain a molded casting sheet;

[0072] (4) preheating the molded cast sheet at 60-80° C., and then longitudinally stretching the sheet at a stretching ratio of (3-6):1 and a stretching temperature of 80-110° C., and cooling the sheet at 30-50° C. after the stretching is completed;

[0073] The cooled film is preheated at 60-80°C, then stretched transversely at a stretching ratio of (2-4):1 and a stretching temperature of 80-110°C, and then cooled at 40-70°C;

[0074] (5) The film sheet treated in step (4) is heat-treated at a temperature of 70-100° C., then air-cooled, and then brought into a winding system through a traction system to be wound up, thereby obtaining the composite polymer film.

[0075] In a third aspect, the present invention provides a current collector, comprising the composite polymer film as described in the first aspect or the composite polymer film prepared by the preparation method as described in the second aspect, and a metal layer arranged on at least one side surface of the composite polymer film.

[0076] In the present invention, the function of the metal layer is to conduct electricity.

[0077] As a preferred technical solution of the present invention, the material of the metal layer includes metal element and / or metal alloy.

[0078] Preferably, the metal element includes any one of elemental copper, elemental aluminum, elemental nickel, elemental titanium or elemental silver, or a combination of at least two of them.

[0079] Preferably, the metal alloy includes any one of copper alloy, aluminum alloy or nickel alloy, or a combination of at least two of them.

[0080] As a preferred technical solution of the present invention, the thickness of the metal layer is 500-2000 nm, for example, it can be 500 nm, 1000 nm, 1500 nm or 2000 nm, etc., preferably 700-1200 nm.

[0081] Preferably, the preparation method of the metal layer includes any one of physical vapor deposition, electroplating or chemical plating, or a combination of at least two of them.

[0082] Preferably, the physical vapor deposition method includes any one of a resistance heating vacuum evaporation method, an electron beam heating vacuum evaporation method, a laser heating vacuum evaporation method or a magnetron sputtering method, or a combination of at least two of them.

[0083] Preferably, a protective layer is provided on the surface of the metal layer at a side away from the composite polymer film.

[0084] It should be noted that when protective layers are provided on both sides of the composite polymer film, the materials of the protective layers on both sides may be consistent or inconsistent, and the thicknesses may be consistent or inconsistent.

[0085] In the present invention, the protective layer is provided to prevent the metal conductive layer from being chemically corroded or physically damaged.

[0086] Preferably, the material of the protective layer includes any one of elemental nickel, elemental chromium, nickel-based alloy, copper-based alloy, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, copper chromate, copper chromite, graphite, carbon black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers or graphene, or a combination of at least two of them.

[0087] Preferably, the thickness of the protective layer is 5-100 nm, for example, 5 nm, 10 nm, 50 nm or 100 nm.

[0088] Preferably, the thickness of the protective layer is ≤ one tenth of the thickness of the metal layer.

[0089] Preferably, the preparation method of the protective layer includes any one of physical vapor deposition, chemical vapor deposition, in-situ forming or coating, or a combination of at least two of them.

[0090] Preferably, the physical vapor deposition method includes vacuum evaporation and / or magnetron sputtering.

[0091] Preferably, the chemical vapor deposition method includes atmospheric pressure chemical vapor deposition and / or plasma enhanced chemical vapor deposition.

[0092] Preferably, the coating method includes any one of die coating, blade coating or extrusion coating.

[0093] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the electrode plate of the lithium-ion battery includes the current collector as described in the third aspect, or includes the current collector made based on the composite polymer film described in the first aspect.

[0094] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0095] Compared with the prior art, the present invention has the following beneficial effects:

[0096] (1) The present invention introduces polyolefin materials into the first polymer layer and the third polymer layer without adding anti-adhesive silica, which can reduce the polarity of the membrane on the one hand, and on the other hand, due to the introduction of polyolefin, the regular arrangement of polyester polymers is destroyed, thereby forming a higher roughness on the membrane surface, reducing the crystallinity of the membrane, and increasing the free volume of the membrane. Therefore, the introduction of polyolefin materials can not only solve the problem of membrane surface adhesion during the winding process caused by the lack of anti-adhesives, but also solve the problem of low adhesion between the metal layer and the composite polymer membrane in the current collector caused by the reduction of membrane polarity, thereby improving the high-temperature cycle performance of the current collector during battery end application. In addition, the three-layer composite polymer membrane constructed by the present invention has good mechanical properties.

[0097] (2) The preparation method provided by the present invention is simple and easy to implement, and can be easily scaled up, which can effectively promote the promotion of the current collector at the application end. DETAILED DESCRIPTION

[0098] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0099] Example 1

[0100] This embodiment provides a composite polymer film for a current collector, the composite polymer film comprising a first polymer layer, a second polymer layer and a third polymer layer stacked in sequence;

[0101] Wherein, the materials of the first polymer layer and the third polymer layer are a combination of a first polyester material and a polyolefin material, and the material of the second polymer layer is a second polyester material;

[0102] The first polyester material and the second polyester material are both polyethylene terephthalate, with a viscosity average molecular weight of 30,000 Da; the polyolefin material is polypropylene, with an isotacticity of 97% and a number average molecular weight of 60,000 Da;

[0103] In the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is 40:60; in the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is 40:60;

[0104] In the second polymer layer, the content of the second polyester material is 100wt%;

[0105] The thicknesses of the first polymer layer, the second polymer layer and the third polymer layer are denoted as h1, h2 and h3 respectively, h1=h3, h1:h2:h3=8:84:8;

[0106] The thickness of the composite polymer film was 4.5 μm.

[0107] This embodiment also provides a method for preparing the composite polymer film, the preparation method comprising the following steps:

[0108] (1) Pre-treating the raw materials for preparing the first polymer layer, specifically comprising the following steps: placing the first polyester material in a crystallizer, crystallizing at 150° C. for 60 minutes, placing the first polyester material in a drying tower after the crystallization treatment is completed, and drying at 160° C. for 160 minutes, placing the polyolefin material in a crystallizer, crystallizing at 80° C. for 100 minutes, placing the first polyester material in a drying tower after the crystallization treatment is completed, and drying at 70° C. for 100 minutes, and then mixing the dried first polyester material and the polyolefin material in a mass ratio of 40:60 to obtain a first material;

[0109] The raw materials for preparing the second polymer layer are pretreated, and the specific steps include:

[0110] The second polyester material is placed in a crystallizer and crystallized at 150° C. for 60 minutes. After the crystallization treatment is completed, the second polyester material is placed in a drying tower and dried at 160° C. for 160 minutes to obtain a second material.

[0111] The raw materials for preparing the third polymer layer are pretreated, and the specific steps include:

[0112] The first polyester material is placed in a crystallizer, and crystallized at 150° C. for 60 minutes. After the crystallization treatment is completed, the first polyester material is placed in a drying tower and dried at 160° C. for 160 minutes. The polyolefin material is placed in a crystallizer, and crystallized at 80° C. for 100 minutes. After the crystallization treatment is completed, the first polyester material and the polyolefin material are mixed in a mass ratio of 40:60 to obtain a third material.

[0113] (2) conveying the first material, the second material and the third material to corresponding twin-screw extruders respectively, heating and melting at 280° C., and then filtering with the aid of a metering pump and co-extruding through a die to obtain a molten material;

[0114] The volume ratio of the extrusion amount of the first material, the second material and the third material is 8:84:8;

[0115] (3) casting the molten material onto a casting roll and cooling it at 30° C. to obtain a molded casting sheet;

[0116] (4) preheating the molded cast sheet at 70° C., and then longitudinally stretching the sheet at a stretching ratio of 4:1 and a stretching temperature of 110° C., and cooling the sheet at 40° C. after the stretching is completed;

[0117] The cooled film was preheated at 80°C, then stretched transversely at a stretching ratio of 3:1 and a stretching temperature of 110°C, and then cooled at 40°C;

[0118] (5) The film sheet treated in step (4) is heat-treated at a temperature of 80° C., and then cooled by air. The film sheet is wound up by a winding system through a traction system to obtain the composite polymer film.

[0119] This embodiment also provides a current collector, which includes the composite polymer film as described above, and a copper layer disposed on both sides of the composite polymer film, wherein a protective layer is disposed on a side of the copper layer away from the composite polymer film;

[0120] The single-side thickness of the copper layer is 1000 nm, the material of the protective layer is chromium oxide, and the single-side thickness of the protective layer is 10 nm.

[0121] This embodiment also provides a method for preparing the above-mentioned current collector, and the preparation method comprises the following steps:

[0122] (a) placing the composite polymer film in a vacuum evaporation chamber, melting and evaporating a high-purity copper wire (purity greater than 99.99%) in a metal evaporation chamber at a high temperature of 1600°C, and the evaporated metal atoms are deposited on both surfaces of the composite polymer film through a cooling system in the vacuum coating chamber to form a copper layer;

[0123] (b) placing the composite film including the copper layer in a dipping solution, wherein the dipping solution is a potassium dichromate aqueous solution (mass concentration is 0.5 g / L), and the dipping time is 30 s. After the dipping is completed, the liquid is squeezed out, and then the composite film is placed in an oven at 60° C. for drying to obtain the current collector.

[0124] Example 2

[0125] The difference between this embodiment and embodiment 1 is that the polyolefin material is ethylene-propylene-butene copolymer.

[0126] The rest of the preparation methods and parameters were the same as those in Example 1.

[0127] Example 3

[0128] The difference between this embodiment and embodiment 1 is that the polyolefin material is a polymer of bicyclo[2,2,1]hept-2-ene and ethylene (CAS: 26007-43-2).

[0129] The rest of the preparation methods and parameters were the same as those in Example 1.

[0130] Example 4

[0131] The difference between this embodiment and embodiment 1 is that both the first polyester material and the second polyester material are polybutylene terephthalate.

[0132] The rest of the preparation methods and parameters were the same as those in Example 1.

[0133] Example 5

[0134] The difference between this embodiment and embodiment 1 is that both the first polyester material and the second polyester material are polyethylene 2,6-naphthalene dicarboxylate.

[0135] The rest of the preparation methods and parameters were the same as those in Example 1.

[0136] Example 6

[0137] The difference between this embodiment and Embodiment 1 is that in the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is 60:40; in the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is 60:40.

[0138] The rest of the preparation methods and parameters were the same as those in Example 1.

[0139] Example 7

[0140] The difference between this embodiment and Embodiment 1 is that in the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is 20:80; in the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is 20:80.

[0141] The rest of the preparation methods and parameters were the same as those in Example 1.

[0142] Example 8

[0143] The difference between this embodiment and embodiment 1 is that the viscosity average molecular weight of the polyethylene terephthalate is 15000 Da.

[0144] The rest of the preparation methods and parameters were the same as those in Example 1.

[0145] Example 9

[0146] The difference between this embodiment and embodiment 1 is that the viscosity average molecular weight of the polyethylene terephthalate is 50000 Da.

[0147] The rest of the preparation methods and parameters were the same as those in Example 1.

[0148] Example 10

[0149] The difference between this embodiment and embodiment 1 is that the number average molecular weight of the polypropylene is 10000 Da.

[0150] The rest of the preparation methods and parameters were the same as those in Example 1.

[0151] Embodiment 11

[0152] The difference between this embodiment and embodiment 1 is that the number average molecular weight of the polypropylene is 100000 Da.

[0153] The rest of the preparation methods and parameters were the same as those in Example 1.

[0154] Example 12

[0155] The difference between this embodiment and embodiment 1 is that h1:h2:h3=1:98:1.

[0156] The rest of the preparation methods and parameters were the same as those in Example 1.

[0157] Example 13

[0158] The difference between this embodiment and embodiment 1 is that h1:h2:h3=15:70:15.

[0159] The rest of the preparation methods and parameters were the same as those in Example 1.

[0160] Embodiment 14

[0161] The difference between this embodiment and Embodiment 1 is that in the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is 65:35; in the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is 65:35.

[0162] The rest of the preparation methods and parameters were the same as those in Example 1.

[0163] Embodiment 15

[0164] The difference between this embodiment and Embodiment 1 is that in the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is 15:85; in the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is 15:85.

[0165] The rest of the preparation methods and parameters were the same as those in Example 1.

[0166] Example 16

[0167] The difference between this embodiment and embodiment 1 is that the viscosity average molecular weight of the polyethylene terephthalate is 13000 Da.

[0168] The rest of the preparation methods and parameters were the same as those in Example 1.

[0169] Embodiment 17

[0170] The difference between this embodiment and embodiment 1 is that the viscosity average molecular weight of the polyethylene terephthalate is 52000 Da.

[0171] The rest of the preparation methods and parameters were the same as those in Example 1.

[0172] Embodiment 18

[0173] The difference between this embodiment and embodiment 1 is that the number average molecular weight of the polypropylene is 9000 Da.

[0174] The rest of the preparation methods and parameters were the same as those in Example 1.

[0175] Embodiment 19

[0176] The difference between this embodiment and embodiment 1 is that the number average molecular weight of the polypropylene is 110000 Da.

[0177] The rest of the preparation methods and parameters were the same as those in Example 1.

[0178] Embodiment 20

[0179] The difference between this embodiment and embodiment 1 is that h1:h2:h3=0.5:99:0.5.

[0180] The rest of the preparation methods and parameters were the same as those in Example 1.

[0181] Embodiment 21

[0182] The difference between this embodiment and embodiment 1 is that h1:h2:h3=17:66:17.

[0183] The rest of the preparation methods and parameters were the same as those in Example 1.

[0184] Embodiment 22

[0185] The difference between this embodiment and embodiment 1 is that the polypropylene is random polypropylene.

[0186] The rest of the preparation methods and parameters were the same as those in Example 1.

[0187] Comparative Example 1

[0188] The difference between this comparative example and Example 1 is that the composite polymer film is a single-layer film, and the material is only polyethylene terephthalate.

[0189] The rest of the preparation methods and parameters were the same as those in Example 1.

[0190] Comparative Example 2

[0191] The difference between this comparative example and Example 1 is that the composite polymer film is a single-layer film, and the material is a combination of polyethylene terephthalate and silicon dioxide, and the contents of the two are 99 wt % and 1 wt %, respectively.

[0192] The rest of the preparation methods and parameters were the same as those in Example 1.

[0193] Comparative Example 3

[0194] The difference between this comparative example and Example 1 is that the composite polymer film is a single-layer film, and the material is a combination of polyethylene terephthalate and polypropylene, and the contents of the two are 40wt% and 60wt% respectively.

[0195] The rest of the preparation methods and parameters were the same as those in Example 1.

[0196] Performance Testing

[0197] 1. The defective rate of the composite polymer films prepared in the above embodiments and comparative examples due to film breakage during the unwinding process, the defective rate of the composite polymer films due to film breakage during the film making process, and the tensile strength of the composite polymer films were tested. The specific test methods are as follows:

[0198] ① Defective rate: the defective rate of the composite polymer film caused by film breakage during the unwinding process, that is, the percentage of the number of defective products caused by film breakage during the unwinding process of the composite polymer film (measured in area) to the total number of products (measured in area); the defective rate of the composite polymer film caused by film breakage during the film making process, that is, the percentage of the number of defective products caused by film breakage during the preparation process of the composite polymer film (measured in area) to the total number of products (measured in area).

[0199] ② The tensile strength of the composite polymer film was tested with reference to standard GB / T 1040.3-2006.

[0200] 2. The adhesion between the composite polymer film and the copper layer in the current collectors prepared in the above embodiments and comparative examples, and the high temperature cycle performance of the battery prepared based on the current collectors were tested. The specific test methods are as follows:

[0201] ① Adhesion: A layer of Permacel P-94 double-sided tape was bonded to a 1 mm thick aluminum foil, the current collector was bonded on top of the double-sided tape, and a layer of ethylene acrylic acid copolymer film (DuPont Nurcel0903, 50 μm thick) was covered on top of the current collector. 5 N / m 2, hot pressing at 120°C for 10s, cooling to room temperature (25°C), and cutting into small strips of 150mm×15mm; finally, the ethylene acrylic acid copolymer film of the sample strip is fixed on the upper fixture of the tensile machine, and the rest is fixed on the lower fixture. After fixation, the two are peeled off at an angle of 180° and a speed of 100mm / min to test the peeling force, that is, the adhesion between the composite polymer film and the copper layer.

[0202] ②High temperature cycle performance:

[0203] i. Assemble lithium-ion batteries: For the positive electrode, the positive electrode current collector uses traditional aluminum foil (thickness 12μm), and the positive electrode material uses LiNi 0.8 Mn 0.1 Co 0.1 O2 (NCM811); for the negative electrode: the negative electrode current collector adopts the current collector prepared by the present invention, and the negative electrode material adopts artificial graphite; for the diaphragm, an alumina ceramic coated polyethylene diaphragm (thickness of 25 μm) is adopted; for the electrolyte, 1 mol·L -1 A carbonate solution of LiPF6, wherein the carbonate comprises propylene carbonate, ethylene carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1; using the above materials, assembling a lithium-ion battery according to a relevant process;

[0204] ii. Test conditions: At 45°C, at a charge and discharge rate of 1C, the battery is cycled for 800 times in the voltage range of 3V to 4.2V, and the battery capacity retention rate after the cycle charge and discharge is recorded.

[0205] The above test results are shown in Table 1.

[0206] Table 1

[0207]

[0208]

[0209] analyze:

[0210] It can be seen from Examples 1-13, Comparative Example 1 and Comparative Example 2 that the composite polymer film prepared by the present invention solves the problem of sticking to the film during unwinding without adding an anti-adhesive agent, and compared with the traditional polymer film with an anti-adhesive added, while ensuring that the film does not stick to the film during unwinding and the tensile strength of the prepared polymer film, the high-temperature charge and discharge performance of the battery prepared based on the current collector of the composite polymer film is improved. This is because the anti-adhesive silica is not introduced into the composite polymer film, and the problem of poor high-temperature charge and discharge cycle performance of the battery caused by the dissolution of silica and the consumption of the electrolyte and its electrochemical reaction products will not occur.

[0211] It can be seen from Example 1 and Comparative Example 3 that, compared with the polymer film of the single-layer structure, the tensile strength of the three-layer composite polymer film prepared by the present invention is significantly improved, and the high-temperature charge-discharge cycle performance of the battery based on the composite polymer film is improved. This is because the thickness of the second polymer layer in the three layers is dominant, and the second polymer layer contains only polyester materials, which can achieve a higher degree of orientation and crystallinity during the biaxial stretching process, ensuring that the prepared composite polymer film has good mechanical properties. In addition, the improvement of tensile strength can reduce the generation of internal defects in the material during the preparation of battery pole pieces by the current collector, thereby further improving the high-temperature charge-discharge cycle performance of the battery.

[0212] It can be seen from Examples 1-5 that replacing polyethylene terephthalate and polypropylene with other types of polyester materials and polyolefin materials can still achieve good inventive effects.

[0213] It can be seen from Examples 1, 6-7 and 14-15 that: a. Increasing the content of polyolefin can reduce the defective rate of the prepared polymer film caused by sticking during the unwinding process. This is because the increase in the content of polyolefin reduces the polarity of the film, resulting in a decrease in surface tension, while the increase in the content of polyolefin destroys the regular arrangement of polyester polymers, thereby forming a higher roughness on the surface of the film. The reduced surface tension and increased roughness jointly alleviate the anti-growth of the sticking film. b. The adhesion between the copper layer in the current collector prepared with this composite polymer film and the composite polymer film first increases and then decreases. This is because when the content of polyolefin is increased, the surface tension of the film decreases, which will lead to a decrease in adhesion. However, when the content of polyolefin is increased, the surface roughness increases, which will cause the adhesion to increase first and then decrease. In addition, when the content of polyolefin is increased, the free volume of the polymer in the film increases, which will also increase the adhesion. The mutual constraints of the three jointly lead to the trend of the adhesion to increase first and then decrease. c. The high-temperature charge-discharge cycle performance of the battery prepared with this current collector first increases and then decreases, which is mainly due to the fact that the adhesion between the copper layer and the composite polymer film in the current collector first increases and then decreases.

[0214] It can be seen from Examples 1, 8-9 and 16-17 that: a. Increasing the molecular weight of the polyester material will first reduce and then increase the defects caused by film breakage during the preparation of the composite polymer film. This is due to the poor film-forming properties caused by the excessively high or low molecular weight of the polyester polymer. b. In the current collector prepared with this composite polymer film as the base film, the adhesion between the composite polymer film and the copper layer first increases and then decreases. This is the result of the mutual constraints of the increase in the molecular weight of the polyester, the decrease in the surface tension of the film and the increase in the surface roughness. c. The high-temperature charge and discharge cycle performance of the battery prepared with this current collector first increases and then decreases. This is mainly due to the fact that the adhesion between the copper layer and the composite polymer film in the current collector first increases and then decreases.

[0215] It can be seen from Example 1, Example 10-11 and Example 18-19 that: a. Increasing the molecular weight of polyolefin will first reduce and then increase the defects caused by film breakage during the preparation of the composite polymer film. This is because the molecular weight of the polyolefin polymer is too high or too low, which makes the film-forming property worse; the surface tension of the prepared composite polymer film remains unchanged, because the surface tension of the film mainly depends on the properties of the polyester polymer; the surface roughness of the prepared composite polymer film increases, because the molecular weight increases, the regular arrangement of the polymer deteriorates during the stretching process, and the crystallinity decreases, resulting in increased roughness. b. In the composite current collector prepared with this composite polymer film as the base film, the adhesion between the composite polymer film and the copper layer increases. This is because the molecular weight of polyolefin increases, the regular arrangement of the polymer deteriorates during the stretching process, resulting in an increase in the surface roughness of the prepared composite polymer film, which is conducive to improving the adhesion between the composite polymer film and the copper layer. c. The high-temperature charge and discharge cycle performance of the battery prepared with this current collector increases, which is mainly due to the increased adhesion between the copper layer and the composite polymer film in the current collector.

[0216] It can be seen from Example 1, Example 12-13 and Example 20-21 that a. Increasing the thickness of the first polymer layer and the third polymer layer will first reduce and then remain unchanged the defects caused by the sticking film of the composite polymer film during the unwinding process. This is because the thickness of the first polymer layer and the third polymer layer is too thin and cannot create a good low surface tension and high roughness surface, resulting in the occurrence of rolling sticking film. b. Increasing the thickness of the first polymer layer and the third polymer layer will reduce the tensile strength of the composite polymer film. This is because the tensile strength of the polyester film mainly depends on the tensile strength of the second polymer layer. When the thickness of the first polymer layer and the third polymer layer is increased, the thickness ratio of the second polymer layer is reduced, resulting in a decrease in tensile strength. c. In the current collector prepared with this composite polymer film as the base film, the bonding force between the composite polymer film and the copper layer first increases and then remains unchanged. This is because with the increase in thickness, the surface tension and roughness of the film first increase and then remain unchanged. d. The high-temperature charge and discharge cycle performance of the battery prepared with this current collector first increases and then decreases. This is due to the combined effect of the bonding force between the copper layer and the composite polymer film in the current collector and the reduction in the tensile strength of the film.

[0217] It can be seen from Example 1 and Example 22 that random polypropylene, on the one hand, is beneficial to reducing the crystallinity of the first and third polymer layers, thereby improving the surface roughness of the prepared polymer film, and on the other hand, it can increase the free volume of the polymer, thereby improving the adhesion between the polymer film and the metal layer in the prepared composite current collector, further improving the cycle performance of the battery.

[0218] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite polymer film for a current collector, characterized in that: The composite polymer film comprises a first polymer layer, a second polymer layer and a third polymer layer stacked in sequence; Wherein, the materials of the first polymer layer and the third polymer layer are a combination of a first polyester material and a polyolefin material, and the material of the second polymer layer is a second polyester material; In the first polymer layer, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80); In the third polymer layer, the mass ratio of the first polyester material to the polyolefin material is (20-60):(40-80); The viscosity average molecular weight of the first polyester material and the second polyester material are independently 15000-50000Da; In the second polymer layer, the content of the second polyester material is 100 wt %.

2. The composite polymer membrane according to claim 1, characterized in that The first polyester material and the second polyester material independently include any one of polyethylene terephthalate, polyethylene 2,6-naphthalate, polybutylene terephthalate, poly-1,4-cyclohexanedimethanol terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol terephthalate, poly-2,6-naphthalate, poly-trimethylene terephthalate, poly-2,6-naphthalate, poly-butylene 2,5-furandicarboxylate or poly-butylene adipate terephthalate or a combination of at least two thereof.

3. The composite polymer membrane according to claim 1, characterized in that The polyolefin material includes any one of polyethylene, polypropylene, polystyrene, ethylene-propylene copolymer, ethylene-propylene-butene copolymer or cyclic olefin copolymer, or a combination of at least two thereof.

4. The composite polymer membrane according to claim 3, characterized in that The polyolefin material is any one of random polypropylene, ethylene-propylene copolymer, ethylene-propylene-butene copolymer or cycloolefin copolymer, or a combination of at least two thereof.

5. The composite polymer membrane according to claim 1, characterized in that The number average molecular weight of the polyolefin material is 10000-100000 Da.

6. The composite polymer membrane according to claim 1, characterized in that The thicknesses of the first polymer layer, the second polymer layer and the third polymer layer are denoted as h1, h2 and h3 respectively, h1=h3, h1:h2=(1-15):(70-98).

7. The composite polymer membrane according to claim 1, characterized in that The thickness of the composite polymer film is ≥1 μm.

8. The composite polymer membrane according to claim 7, characterized in that The composite polymer film has a thickness of 2-20 μm.

9. A method for preparing a composite polymer film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The raw materials for preparing the first polymer layer, the second polymer layer and the third polymer layer are respectively added into corresponding extrusion equipment, and after melt co-extrusion, they are successively subjected to sheet casting, stretching treatment and heat treatment, and the composite polymer film is obtained after winding.

10. The preparation method according to claim 9, characterized in that: Before the raw materials for preparing the first polymer layer are added to the corresponding extrusion equipment, the raw materials for preparing the first polymer layer are pretreated, and the specific steps include: The first polyester material is crystallized and dried, the polyolefin material is crystallized and dried, and then the dried first polyester material and the polyolefin material are mixed.

11. The preparation method according to claim 9, characterized in that: Before the raw materials for preparing the second polymer layer are added to the corresponding extrusion equipment, the raw materials for preparing the second polymer layer are pretreated, and the specific steps include: The second polyester material is crystallized and dried.

12. The preparation method according to claim 9, characterized in that: Before the raw materials for preparing the third polymer layer are added to the corresponding extrusion equipment, the raw materials for preparing the third polymer layer are pretreated, and the specific steps include: The first polyester material is crystallized and dried, the polyolefin material is crystallized and dried, and then the dried first polyester material and the polyolefin material are mixed.

13. The preparation method according to claim 9, characterized in that: During the melt co-extrusion process, the heating and melting temperature is 270-290°C.

14. The preparation method according to claim 9, characterized in that: During the melt co-extrusion process, the volume ratio of the extruded amounts of the raw materials for preparing the first polymer layer, the second polymer layer and the third polymer layer is (1-15):(70-98):(1-15).

15. The preparation method according to claim 9, characterized in that: The stretching treatment includes longitudinal stretching and transverse stretching.

16. The preparation method according to claim 15, characterized in that: The stretching ratio of the longitudinal stretching is (3-6):1, and the stretching temperature of the longitudinal stretching is 80-110°C. The stretching ratio of the transverse stretching is (2-4):1, and the stretching temperature of the transverse stretching is 80-110°C.

17. The preparation method according to claim 9, characterized in that: The temperature of the heat treatment is 70-100°C.

18. The preparation method according to claim 9, characterized in that: The preparation method comprises the following steps: (1) Pre-treating the raw materials for preparing the first polymer layer, specifically comprising the following steps: crystallizing the first polyester material at 130-200° C. for 20-130 min, then drying at 130-180° C. for 110-300 min, crystallizing the polyolefin material at 60-100° C. for 20-120 min, then drying at 60-80° C. for 100-300 min, and then mixing the dried first polyester material and the polyolefin material to obtain a first material; The raw materials for preparing the second polymer layer are pretreated, and the specific steps include: The second polyester material is crystallized at 130-200° C. for 20-130 min, and then dried at 130-180° C. for 110-300 min to obtain a second material; The raw materials for preparing the third polymer layer are pretreated, and the specific steps include: The first polyester material is crystallized at 130-200° C. for 20-130 min, and then dried at 130-180° C. for 110-300 min, the polyolefin material is crystallized at 60-100° C. for 20-120 min, and then dried at 60-80° C. for 100-300 min, and then the dried first polyester material and the polyolefin material are mixed to obtain a third material; (2) conveying the first material, the second material and the third material to corresponding twin-screw extruders respectively, heating and melting at 270-290° C., filtering and co-extruding through a die head to obtain molten materials; Wherein, the volume ratio of the extrusion amount of the first material, the second material and the third material is (1-15):(70-98):(1-15); (3) casting the molten material onto a casting roll, and cooling the molten material at 20-60° C. to obtain a molded casting sheet; (4) preheating the molded cast sheet at 60-80°C, and then longitudinally stretching the sheet at a stretching ratio of (3-6):1 and a stretching temperature of 80-110°C. After the stretching, the sheet is cooled at 30-50°C; The cooled film is preheated at 60-80°C, then stretched transversely at a stretching ratio of (2-4):1 and a stretching temperature of 80-110°C, and then cooled at 40-70°C; (5) The film sheet treated in step (4) is heat-treated at a temperature of 70-100° C., and then air-cooled. The film sheet is then wound up by a winding system through a traction system to obtain the composite polymer film.

19. A current collector, characterized in that: The current collector comprises the composite polymer film according to any one of claims 1 to 8 or the composite polymer film prepared by the preparation method according to any one of claims 9 to 18, and a metal layer disposed on at least one side surface of the composite polymer film.

20. The current collector according to claim 19, characterized in that: The thickness of the metal layer is 500-2000nm.

21. The current collector according to claim 20, characterized in that: The thickness of the metal layer is 700-1200 nm.

22. The current collector according to claim 19, characterized in that: A protective layer is arranged on the surface of the metal layer which is away from the composite polymer film.

23. The current collector according to claim 22, characterized in that: The material of the protective layer includes any one of elemental nickel, elemental chromium, nickel-based alloy, copper-based alloy, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, copper chromate, copper chromite, graphite, carbon black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers or graphene, or a combination of at least two of them.

24. The current collector according to claim 22, characterized in that: The thickness of the protective layer is 5-100 nm.

25. A lithium ion battery, characterized in that: The electrode plate of the lithium-ion battery includes the current collector according to any one of claims 19 to 24, or includes the current collector made based on the composite polymer film according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Solvent-resistant enhanced polyester film, preparation method thereof, composite current collector and application

    CN115322534A

  • PET sheet production process

    CN1850491A